Screening of bread wheat cultivars (Triticum aestivum L.) to water deficit stress under field conditions - Al-Temimi, Hamed; Al-Shahwany, Ayyad; Alsaadawi, Ibrahim (Iraqi Journal of Science, 2023)
Field trial was conducted during the growing season of 2011-2012 at the ResearchField, Department of Biology, College of Science, Baghdad University to test theperformance of wheat cv Rabyaa, Latifiya, Al-Iraq, Tummose 2, Abu-Graib 3, IPA99 and Sham 6 grown under different soil water deficit stresses. Several agronomicand physiological traits and yield and yield components of the test cultivars weredetermined. The experiment was conducted in split plot design with five replicationsfor each treatment. The cultivars were kept in the sub plot while water stresstreatment was assigned as main plot. Water stress was applied by irrigated the plotsto the soil field capacity (FC) then withheld next irrigation until the soil moisture ofthe respective plots depleted to 50 (control), 25 and 15% of FC.Results indicated that the water deficit stress significantly reduced biological yield,grain yield and yield components, plant height and number of tillers. Also, droughtsignificantly reduced leaf area and chlorophyll content and increased prolineaccumulation of the all test cultivars. In most cases, the reduction increased with theincreased water stress. The results also showed significant differences among thetest cultivars in most of the aforementioned parameters. Under higher drought stress,cultivars Rabyaa, Latifiya and Abu-Graib 3 were superior in grain and biologicalyields and most of yield components (number of spikes/m2, number of grains/spikeand 1000-grain weight) compared to other cultivars including Sham 6 and IPA 99which recorded lower values of these traits. Subsequent analyses revealed thedrought tolerant cultivars (Rabyaa, Latifiya and Abu-Graib 3) showed increasedwith high significant in grain and biological yields, yield components, plant height,number of tiller, leaf area, accumulation of proline and total chlorophyll content thannon-tolerant cultivars (Sham 6 and IPA 99). This suggests that the these charactersare useful criteria that may be used for screening wheat genotypes for droughttolerance.